The impact of forensic genetics on the management of sexual assault victims: A multicentre GE.F.I project. Issue 1 (December 2019) - Gino, Sarah; Bo, Marco; Ricciardelli, Rossana; Alù, Milena; Boschi, Ilaria; Carnevali, Eugenia; Fabbri, Matteo; Fattorini, Paolo; Piccinini, Andrea; Previderè, Carlo; Verzeletti, Andrea; Tozzo, Pamela; et al.
Abstract: We conducted a retrospective study to analyse the ways in which sexual abuse was handled by the Italian forensic geneticists in order to delineate common strategies in the management of the collected biological samples. In particular, the results of laboratory analyses were compared with the patients' reports and the outcome of their medical examination, as recorded on standard evidence collection documents. The purpose of this study is identifying which factors could influence the congruence between what was reported and the typing of male genetic profiles. The project was proposed at the Italian Society of Forensic Genetics and 10 laboratories have joined the study filling in a questionnaire. We analysed 102 cases that occurred between 2006 and 2017. The analysis of the data here presented highlights that the ability to ascertain the presence of male biological material in the collected evidence is not a technical problem for forensic genetics laboratories but it seems to be influenced by other factors, such as how much time elapsed before being taken into care, actions or other relevant events that have occurred between the assault and the medical examination, and the characterisation of the evidence.